Availability Evaluation of Microprocessor Relay Protection - Michael Uspensky (Recent Advances in Mathematical Research and Computer Science Vol. 9, 2022)
The quantitative assessment attempt of availability indicators for the specific microprocessor structure of the relay protection system by analogy with an assessment of similar digital systems in other industries is given in this work. In the given work, the reliability indicators of the original backup structure for a specific digital protection system were assessed, at that its hardware was assessed without taking into account the software reliability. The reliability models of system components are provided. The calculation sequence is shown. Calculation results give an optimistic evaluation of such protection creation and indicate the influence of the number of autonomous protection blocks reserved by the central protection and recovery time on the system availability.